Participatory Humanistic Leadership and Teacher’s Professional Development in State Islamic Junior High Schools - Eci Sriwahyuni; Jasrial Jasrial; Syahril Syahril (Journal of Social Work and Science Education, 2026)
This study aims to examine in depth the practice of humanism-based participatory leadership in the development of teaching staff professionalism at MTsN 17 Tanah Datar. The study employed a qualitative approach with a case study design. Data were collected through passive participant observation, in-depth interviews, and documentation. The principal of the madrasah served as the key informant, while supporting informants were selected using the snowball sampling technique. Data validity was ensured through source and technique triangulation as well as member checking, while data analysis was conducted using the Miles and Huberman interactive model. The findings indicate that humanism-based participatory leadership at MTsN 17 Tanah Datar is manifested through collective participation in program planning, collaborative dialogue, humanistic role modeling, mentoring in digital transformation, dialogical academic supervision, task distribution based on individual potential, and the provision of rewards and emotional support. These practices significantly contribute to the enhancement of teacher professionalism, the strengthening of motivation and professional autonomy, and the creation of an inclusive and collaborative organizational climate. This study integrates participatory leadership, a humanistic approach, and Islamic values within the context of madrasah education. Practically, the findings offer a leadership model that may serve as a reference for madrasah principals in sustainably developing the professionalism of teaching staff. Theoretically, this study enriches the discourse on educational leadership by providing a contextual humanistic-religious perspective.